The Best Solvent And Extraction Time In Pectin Production made From Waste Of Jackfruit (Bark and Straw) - Wignyanto Wignyanto; Nur Lailatul Rahmah (APTA and DTIP FTP UGM, 2017)
Jackfruit barks are known to have fairly high pectin content, by 4.7% on wet and 22.5% on dry barks. The content is sufficiently highboy make it worthy of being raw material for producing pectin. Pectin is a polygalacturonic acid containing methyl ester. Pectin is a high- value functional food that is widely used as gelling agent and stabilizer. Approximately 65 until 80% jackfruit barks were wasted from the industry and it were only useful for animal feed . To increase the added value of it, so that jackfruit barks were extracted to get the pectin. This research used randomized block design (RBD) with 2 factors:(i)the type of solvents(hydrochloric and citric acids, with pH = 1.5) and (ii) extraction times (30, 90 and 150 minutes). Each factor is conducted in triplicate in order to get 18 units of experiment. Before analyzed, the jackfruit waste (bark and straw) was powdered during sample preparation. Later on, the yield, equivalent weight, methoxyl, galacturonic acid, and ash contents of the powdered, then were analyzed and used as pectin’s parameters. Multiple attribute method (Zeleny method) was used to determine which combination of treatments that produced pectin with the best pectin’s parameter. The best pectin made from jackfruit waste is derived from the combination of citric acid solvent and the extraction time of 150 minutes, resulting in yield of 10.21%, methoxyl content of 9.25%, equivalent weight of 1088.43 g/mol, ash content of 2.79%, and galacturonic acid content of 47.40%.